Analisa Pengendalian Kualitas Menggunakan Metode Seven Tools untuk Meminimalkan Return Konsumen di PT. XYZ - Indah Nursyamsi; Ade Momon (Jurnal Serambi Engineering, 2022)
To overcome quality problems regarding product defects that occur in the company, it is necessary to do an analysis related to the problems that occur and it is necessary to plan improvements to reduce consumer returns. This study aims to analyze and plan improvement plans using the Quality Control Circle (QCC) method using Seven Tools. The Seven Tools used consist of a check sheet, run chart, histogram, scatter diagram, Pareto diagram, cause and effect diagram (fishbone diagram), and control chart. The research was conducted using the interview method with the parties involved with the object and problem. The research data taken is the company's historical data in 2020. The results show that product defects can be caused by various factors such as humans, machines, climate or weather and storage methods. The criteria for defects that often occur in the company are damaged products due to fractures, rusty products, and product sizes that do not match. It can be seen from the criteria for these defects, improvements that can be made are by providing suggestions to overcome the problem so as to reduce the returns that occur in the company.